2007
DOI: 10.1158/1078-0432.ccr-07-0472
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Subset of CD4+CD25highFoxp3+ T Cells Secreting Interleukin-10 and Transforming Growth Factor-β1 Mediates Suppression in the Tumor Microenvironment

Abstract: + subset, CD25 high Treg represented 3 F 0.5% inTIL, 1 F 0.3% in PBMC, and 0.4 F 0.2% in normal controls. Tregs in TIL were GITR + , IL-10 + , and TGF-h1 + , although circulating Treg up-regulated CD62L and CCR7 but not GITR, IL-10, or TGF-h1. Treg in TIL mediated stronger suppression (P V 0.001) thanTreg in PBMC of HNSCC patients. The addition of neutralizing IL-10 and TGF-h antibodies almost completely abrogated suppression (5 F 2.51%). Transwell inserts partly prevented suppression (60 F 5% versus 95 F 5%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
318
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(334 citation statements)
references
References 42 publications
8
318
0
8
Order By: Relevance
“…However, macrophages are not the sole IL-10 source in tumors. Studies in human cancer have shown that Treg cells recruited at tumor sites produce abundant IL-10 [37,38], which may work as the main mediator of Treg-cell functional suppression [37]. Conversely, in a murine tumor model, others have shown that CD25 1 -cell depletion and IL-10 receptor blockade exert distinct, though partially overlapping, effects in suppressing DC activation and anti-tumor CD8 1 response [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, macrophages are not the sole IL-10 source in tumors. Studies in human cancer have shown that Treg cells recruited at tumor sites produce abundant IL-10 [37,38], which may work as the main mediator of Treg-cell functional suppression [37]. Conversely, in a murine tumor model, others have shown that CD25 1 -cell depletion and IL-10 receptor blockade exert distinct, though partially overlapping, effects in suppressing DC activation and anti-tumor CD8 1 response [13].…”
Section: Discussionmentioning
confidence: 99%
“…W światowym piśmiennictwie liczni badacze wskazują na znaczącą rolę badań nad zaburzeniami układu odpornościowego w przebiegu choroby nowotworowej [10][11][12][13][14][15][16][17][18][19][20][21][22]. Dokładne poznanie i zrozumienie mechanizmów tych zaburzeń stwarza szansę na wskazanie immunologicznych wykładników związanych z klinicznym przebiegiem choroby, na podstawie których można by oceniać stopień inwazyjności zmian nowotworowych i podejmować właści-we decyzje terapeutyczne.…”
Section: Wstępunclassified
“…Znaczenie tych czynników w onkologii klinicznej opiera się na ich różnorodnych właściwościach modyfikowania odpowiedzi immunologicznej. Najczęściej wskazywanymi cytokinami, które mogą mieć znaczenie w przebiegu choroby nowotworowej, są interleukiny o właściwościach prozapalnych IL-6 i IL-8 oraz cytokiny IL-10 i TGF-β o działaniu regulatorowym i immunosupresyjnym [19,21,23,[33][34][35]. Prozapalne cytokiny IL-6 i IL-8 wydzielane przez komórki nowotworowe, określane jako czynniki promujące kancerogenezę i wzrost guza nowotworowego, oraz cytokiny o właściwościach proonkogennych i prometastatycznych sprzyjają w szczególny sposób progresji choroby nowotworowej, w tym HNSCC [18,23,[35][36][37][38].…”
Section: Wstępunclassified
“…1) are also seen in the circulation [38,39]. Tregs within the tumor mediate suppression through TGF-β and/or IL-10, compromising tumor-specific CD8 + responses [38].…”
Section: Regulatory T Cells and Tgf-βmentioning
confidence: 99%
“…In one report, increased Treg prevalence in HNSCC was surprisingly associated with a better disease prognosis [46], requiring further elucidation. Response to treatment has been linked to an expansion of Tregs in the circulation, although this may not be indicative of what occurs within the tumor sites [38]. The balance between helper T cells and Treg has also been shown to be a critical parameter in the response to cancer vaccines [47].…”
Section: Regulatory T Cells and Tgf-βmentioning
confidence: 99%